Synthesis of the Isoxazolo[4,3,2-de]phenanthridinone Moiety of the Parnafungins - Zhou, Quan (2009)
[Image: see text] A practical route to the labile tetracyclic isoxazolo[4,3,2-de]phenanthridinone moiety of the antifungal parnafungins has been developed. Zinc reduction of a methyl 2'-hydroxymethyl-2-nitro-3-biphenylcarboxylate, which was prepared by a Suzuki coupling, afforded a benzisoxazolone that was treated with MsCl and base to generate the labile tetracyclic ring system in 37–47% yield. This compound decomposes to the phenanthridine in CDCl(3) and the phenanthridine N-oxide in aqueous base.